Mapping Policymaker Perspectives Of The Climate Security- Migration Nexus In Nigeria: A Social Media Analysis - Carneiro, Bia; Pacillo, Grazia; Läderach, Peter R.D.; DuttaGupta, Tanaya; Resce, Giuliano (CGIAR FOCUS Climate Security, 2022)
Despite growing attention around the climate security-migration nexus, the linkages between climate change, migration, and conflict and security risks have remained a matter of debate for research, policy, and practice. Attempts at gathering empirical evidence on this nexus, as well as global level policy instruments, have mainly focused on international contexts. At national and sub-national scales, interest and awareness around this nexus has yet to be reflected in the policy arena. Not only are the development of policies for national and human security and for climate adaptation and mitigation often detached, they largely fail to consider the complex pathways that connect these two dimensions with human mobility and immobility. To address this gap, we apply an online issue mapping approach to assess representations of migration as a topic of governance within the public discourse of state actors related to climate security domains, using Nigeria as a case study. This study investigates two research questions: 1) How is the climate security-migration nexus represented in Nigeria’s policy agenda? 2) What associations between migration and other climate security variables are represented in the public discourse of policymakers? In line with recent trends in academic research that use social media platforms as proxies for wider public discourse and engagement, this study relies on the foundations of Digital Methods to explore the salience of the climate security-migration nexus among Nigerian policy actors at national level.